METHANE EMISSION VIS-A-VIS LIVESTOCK AND MITIGATION STRATEGIES- A REVIEW (Indian Journal of Animal Production and Management, 2013)
It has been noted thta livestock sector is growing faster than any other agricultural sub-sector and it contributes about 40% to global agriculral output. Livestock has made an important contribution to the food supplies globally through various products like milk, meat eggs, etc. The production of livestock products over the pas two decades (FAO, 2006) is increasing fastly, particularly in developing countries; reported an increase of 78%, 127% and 331% in cereal, meat and egg production, respectively.
Keywords: METHANE; VIS-A-VIS; STRATEGIES- A REVIEW